2011
DOI: 10.1063/1.3604391
|View full text |Cite
|
Sign up to set email alerts
|

Amplitude-modulated sinusoidal microchannels for observing adaptability in C. elegans locomotion

Abstract: In this paper, we present a movement-based assay to observe adaptability in Caenorhabditis elegans locomotion behavior. The assay comprises a series of sinusoidal microchannels with a fixed wavelength and modulating ͑increasing or decreasing͒ amplitude. The channel width is comparable to the body diameter of the organism. Worms are allowed to enter the channel from the input port and migrate toward the output port. Within channel sections that closely match the worm's natural undulations, the worm movement is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 28 publications
2
21
0
1
Order By: Relevance
“…Values indicate nematode crawling behaviour comparable to data reported for smooth crawling. 35,44 ments. This variation in the undulation frequency verifies that the worm responds to different geometric constraints imposed by the pillar arrangement through changes in the period at which it flexes its dorsal-ventral body wall muscles.…”
Section: Measurement Of Other C Elegans Locomotion Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Values indicate nematode crawling behaviour comparable to data reported for smooth crawling. 35,44 ments. This variation in the undulation frequency verifies that the worm responds to different geometric constraints imposed by the pillar arrangement through changes in the period at which it flexes its dorsal-ventral body wall muscles.…”
Section: Measurement Of Other C Elegans Locomotion Parametersmentioning
confidence: 99%
“…In particular, a series of sinusoidal microchannels with varying amplitudes and wavelengths was used to match the worm sinusoidal movement. 35 Their suggested methods can be used as a screening system for locomotion phenotypes. As previously mentioned, C. elegans locomotion is highly dependent of its environment.…”
Section: Introductionmentioning
confidence: 99%
“…8,9,[12][13][14][15][16][17] Moreover, microfluidic devices can be automated to handle single or a population of C. elegans in a high-throughput fashion, which enables large-scale assays such as drug and genetic screens. [15][16][17][18][19][20][21][22] In previous work from our group, we designed a simple microfluidic device to examine the swimming behaviors of C. elegans under electric fields, termed electrotaxis, and demonstrated that changes in movement are reliable indicators of neurodegeneration and harmful effects of toxic chemicals on C. elegans health. [23][24][25] However, the inherent manual operation of the devices makes the screening process labor intensive and time consuming, which limits largely the practical application of the method.…”
Section: Introductionmentioning
confidence: 99%
“…Crawling is the undulatory, sinusoidal movement of a worm that results in forward or backward locomotion. 33 Curling, as defined earlier, occurs when the worm's head touches or overlaps its tail. Flailing happens when a worm oscillates its body in half waves about a fixed location and is an unusual swimming-like behavior we observed in 0.8% agarose gel.…”
Section: A Frequency Of Body Curlsmentioning
confidence: 98%